Studies on Neotropical Fauna and Environment - Studies on Neotropical Fauna and Environment (Taylor & Francis, 2026)
There is still a far from complete understanding of the complex ecosystems in the Neotropics, although they have been studied since the first expeditions of the old world naturalists Marcgrave, Humboldt, Spix, Darwin, Bates and Müller. The aims and scope of the Journal are, besides taxonomic and zoogeographic surveys, analyses of animal communities and their relationship with biotic and abiotic environmental conditions. This includes the fauna of both terrestrial and fresh water ecosystems in the Neotropics. Contributions that represent original research and mini-reviews are welcome.
FI 0.45
Q3
Keywords: Biological; Earth & Environmental Food Science; Acuerdos transformativos; Transformative agreements; Ecología neotropical; Fauna; Ecosistemas terrestres; Agua dulce